Maraknya Bullying Yang Terjadi Di Sekolah Dasar (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
Bullying in elementary schools has become an increasingly serious problem in recent years. Bullying behaviors, such as physical, verbal and psychological abuse, can have a significant negative impact on children's development. This study aims to identify the factors that cause bullying in elementary schools and evaluate effective prevention and treatment strategies. The research method used is library research, which is a research method by collecting data by understanding and studying theories from various literatures related to the research. The results showed that the factors causing bullying in elementary schools include: lack of supervision and intervention from the school, peer influence, and unfavorable family conditions. To overcome the problem of bullying, a comprehensive effort is needed that involves all elements of the school, family and community. Some recommended strategies are: increasing the capacity of teachers in handling bullying cases, developing anti-bullying programs that are integrated in the school curriculum, and empowering parents and communities to play an active role in preventing and dealing with bullying.